Magnetic metal-organic frameworks for efficient removal of cadmium(II), and lead(II) from aqueous solution. Issue 3 (June 2022) - Abdel-Magied, Ahmed F.; Abdelhamid, Hani Nasser; Ashour, Radwa M.; Fu, Le; Dowaidar, Moataz; Xia, Wei; Forsberg, Kerstin
Abstract: Efficient and convenient methods for the removal of toxic heavy metal ions especially Cd(II) and Pb(II) from aqueous solutions is of great importance due to their serious threat to public health and the ecological system. In this study, two magnetic metal-organic frameworks (namely: Fe3 O4 @ZIF-8, and Fe3 O4 @UiO-66–NH2 ) were synthesized, fully characterized, and applied for the adsorption of Cd(II) and Pb(II) from aqueous solutions. The adsorption efficiencies for the prepared nanocomposites are strongly dependent on the pH of the aqueous solution. The maximum adsorption capacities of Fe3 O4 @UiO-66–NH2, and Fe3 O4 @ZIF-8 at pH 6.0 were calculated to be 714.3 mg·g −, and 370 mg·g −1 for Cd(II), respectively, and 833.3 mg·g −1, and 666.7 mg·g −1 for Pb(II), respectively. The adsorption process follows a pseudo -second-order model and fit the Langmuir isotherm model. Moreover, the thermodynamic studies revealed that the adsorption process is endothermic, and spontaneous in nature. A plausible adsorption mechanism was discussed in detail. The magnetic adsorbents: Fe3 O4 @ZIF-8, and Fe3 O4 @UiO-66–NH2 showed excellent reusability, maintaining the same efficiency for at least four consecutive cycles. These results reveal the potential use of magnetic Fe3 O4 @ZIF-8, and Fe3 O4 @UiO-66–NH2 as efficient adsorbents in removing Cd(II) and Pb(II) from aqueous solutions. Graphical Abstract: ga1 Highlights: Two magnetic metal-organic frameworks were synthesized and characterized. Adsorption of Cd(II) and Pb(II) from aqueous solutions were assessed. Adsorption kinetics and mechanisms were analyzed.